(untitled) (The Journal of Plant Protection Sciences, 2023)
Among the reasons for the low yield of potato in Bangladesh, lack of disease free quality seed tubers, lack of improved varieties/ practices and disease problems are noticeable (4). The total seed potato requirement of Bangladesh is estimated at about 7.50 lakh tons per annum. Locally produced certified seed meets about 6% of the total requirement (10). Every year about 10,000 tons of potato seeds are being imported with a very high ex pense of foreign currency. Farmers, traders or cold storage owners supply the remaining seed. The cost of good quality planting mate rials produced and sold by the Bangladesh Agricultural Development Corporation (BADC) and private farms are beyond the reach of poor farmers. Therefore, the farmers are forced to acquire poor quality seed from the informal system. In the seed plot tech nique (SPT), disease free potato seed tuber (whole tuber), early planting, maintaining iso lation distance by planning non host (wheat) surrounding the seed plot, use of HYV disease resistant varieties, roughing diseased plant at 30-45 days after planting (DAP), spraying insecticide (Admire) for vector control, spray ing fungicides to minimize fungal diseases, weeding, other improve management, haulm pulling at 80DAP, harvesting, sorting, grad ing, seed treating with boric acid (3%) and storing at cold store found most effective in producing disease free seed potatoes at farm ers’ field at different locations (2). Efforts to increase the quality of planting materials, pro duction techniques in the informal system will help the resource poor farmers by making available quality planting material, higher yields and finally alleviate poverty. Hence, farmers’ field trials was undertaken to im prove the informal seed system in potato seed growing areas of Bangladesh, and to provide farmers with an alternative source for quality planting materials at a reasonable price.